The babylonian period in Judah: in search of the half full cup - Lipshits, ʿOded (The journal of Hebrew scriptures, 2007)
This conversation with O. Lipschits, The Fall and Rise of Jerusalem (Winona Lake, Ind.: Eisenbrauns, 2005) began at a session of the “Literature and History of the Persian Period” group at the 2005 Annual Meeting of the Society of Biblical Literature in Philadelphia. It includes an introduction by the editor and contributions by Rainer Albertz, Tamara Cohn Eskenazi, Daniel Master, Gary N. Knoppers, Hugh G.M. Williamson and a response by Oded Lipschits.